A new excavation analysis method for slope design using discrete fracture network based polyhedral modelling. (June 2016) - Elmouttie, Marc; Krähenbühl, Grégoire; Soliman, Ahmed
Abstract: A method to analyse potential excavation geometries, termed excavation isoplethogram, has previously been proposed for use in civil or mining engineering. The results are typically presented in the form of a contour plot identifying orientations of proposed excavation planes that may lead to large volumes (or masses) of unstable blocks and wedges. In this paper, a novel algorithm is proposed to utilise the probabilistic discrete fracture network approach to quantify the risk associated with various slope designs. The method is applied using open cut mine data in order to demonstrate its potential for decision making in mine design and operations.